Praying for the Liberation of the Holy Sepulchre: Franciscan Liturgy in Fifteenth Century Jerusalem - Valentina Covaci (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2019)
The fall of Jerusalem to Saladin in 1187 and the loss of the Frankish Levant in 1291 triggered new calls or crusade and the literature dedicated to "the recovery of the Holy Land" (pro recuperatione Terre Sancte). The exhortation to war and the urgency of Jerusalem's deliverance were also expressed through liturgy. This article examines two liturgical texts, a "Votive mass for the recovery of the Holy Land" (Missa devota ad recurandam Terram Sanctam) and an "Introit to the Holy Sepulchre of the Lord" (Ad Sanctum Sepulcrum Donin introitus), transmitted in manuscripts from the Franciscan library in Jerusalem, the Biblioteca Generale della Custodia di Terra Santa. This article explores the two liturgical texts in the historical context of fifteenth-century Jerusalem, when the Franciscan friars where the only Latin clergy allowed to serve at the Holy Places. Historical accounts produced in this milieu evince the friars' efforts to memorialize the deeds of the crusader kings, celebrated as liberators of the Holy Land. The liturgical texts analysed here complement this militant memorialization.